Land governance and women's rights in large-scale land acquisitions in Cameroon. Issue 4 (18th May 2016) - Fonjong, Lotsmart; Sama-Lang, Irene; Fombe, Lawrence; Abonge, Christiana
ABSTRACT: This article identifies and examines the role of actors involved in the process of large-scale land acquisitions in Cameroon. It is based on primary data from interviews conducted among principal actors. Findings reveal that government, chiefs, and to some extent elites, play key roles in formal and informal processes that grant land to investors. However, both processes neglect women and affected communities because there are no mechanisms to hold actors accountable to them, especially to women who depend on land for their livelihood. The article concludes that a legal framework that makes the process transparent and promotes accountability and gender inclusiveness is indispensable.